Evidence For In Vitro and In Situ Pyrite Weathering By Microbial Communities Inhabiting Weathered Shale. Issue 7 (9th August 2019) - Samuels, Toby; Pybus, David; Wilkinson, Mark; Cockell, Charles S.
Abstract: Microbial pyrite oxidation is an important driver of biological weathering within shale, making a significant contribution toward biogeochemical cycling, bedrock expansion, and soil formation. These processes are of global importance, both within natural systems and in anthropogenic environments. Despite its significance, there is a lack of research that directly investigates microbe– pyrite interactions within shale. In this study, we use both field and laboratory approaches to inspect microbial pyrite oxidation in weathered shale environments within North Yorkshire, UK. Incubation of polished pyrite samples within iron-oxidizing enrichment cultures in vitro resulted in extensive colonization and surface pitting, demonstrating the weathering potential of shale microbial communities. Mineral samples were buried for 1 year within the floor of a shale rock mine, to explore pyrite bioweathering in situ . Image analysis revealed the formation of dissolution channels by microbial filaments, a novel mechanism of pyrite oxidation that broadens the taxonomic range of known microbe-pyrite interactions in weathered shale.